Mitigating fatigue in long COVID patients with MYPplus: a clinical observation - Yu-Jin Choi; Jin-Seok Lee; Jin-Yong Joung; Seung-Ju Hwang; Young-Yil Kim; Chang-Gue Son (BMC Infectious Diseases)
Abstract Purpose The COVID-19 pandemic has led to the emergence of a secondary public health crisis known as Long COVID. It is estimated that approximately 10% of individuals who contact COVID-19 develop Long COVID, with fatigue and brain fog being among the most commonly reported and debilitating symptoms. However, no standardized or effective treatments are currently available. This observational study aimed to evaluate the efficacy of MYPplus, an herbal formulation composed of Astragali Radix, Salviae Radix, and Aquilariae Lignum, in alleviating fatigue and brain fog in patients with Long COVID. Methods Subjects with a score of 60 or higher on the Modified Korean version of the Chalder Fatigue scale (mKCFQ11) or a brain fog rating of 5 or higher on the visual analogue scale (VAS) took two capsules of MYPplus (500 mg per capsule) twice daily for 4 weeks. Changes in symptoms were assessed using the mKCFQ11, Multidimensional Fatigue Inventory (MFI-20), Fatigue VAS, Brain fog VAS, and overall quality of life using the Short-Form Health Survey (SF-12). Additionally, levels of three cytokines (TNF-α, TGF-β, IFN- γ) and cortisol were measured. Results Fifty participants successfully completed the 4-week administration with MYPplus. At baseline, fatigue severity was 75.3 ± 10.9 in mKCFQ11, 70.9 ± 11.2 in MFI-20, 7.5 ± 1.2 in Fatigue VAS, 8.4 ± 1.1 in Brain fog VAS, and 45.3 ± 17.8 in SF-12. All parameters significantly improved (p < 0.01), with a decrease of 46% in mKCFQ11, 26% in MFI-20, 49% in Fatigue VAS, and 52% in Brain fog VAS, and an increase of 59% in SF-12, respectively. Unlikely others, the plasma level of TGF-β showed a declining pattern after MYPplus administration (from 765.0 ± 1759.7 to 243.9 ± 708.1 pg/mL, p = 0.07). No safety concerns were observed. Conclusion This pilot observational study suggests the clinical potential of MYPplus for managing patients with Long COVID, focusing on fatigue-related symptoms and quality of life. Further studies are required to confirm its efficacy and safety using large-scale randomized placebo-controlled trials in the future. Protocol registration This study has been retrospectively registered with the identifier number KCT0008948 on https://cris.nih.go.kr , as of 27/10/23.